The Influence of Lecturer Discipline on Student Learning Satisfaction in The History Education Study Program Faculty of Teacher Training and Education Tadulako University - Natasya; Rore, Idrus A; Suyuti; Lumangino, Wilman Darsono (Kirana Publisher (KNPub), 2025)
This study aims to explain the influence of lecturer discipline on student learning satisfaction in the History Education Study Program, FKIP, Tadulako University. The type of research used is Quantitative research, the sampling technique is simple random sampling, the research sample amounted to 100 out of 410 student populations using data collection techniques through a questionnaire in the form of a google form. The results of the study show that based on the results of data analysis using SPSS (version 26) the results of the Spearman's correlation coefficient (ρ) = 0.514, Significance value (p-value) = 0.000, Number of respondents (n) = 100, Degrees of freedom (df) = 98, t count = 5.935, and t table (α = 0.05 two parties) = 1.984. The ρ value of 0.514 indicates that the relationship between the two variables is positive and is in the moderate category. This means that the higher the lecturer's discipline, the higher the level of student learning satisfaction. A significance value of 0.000 (less than 0.05) indicates that the relationship is statistically significant, so the null hypothesis (H₀) is rejected and the alternative hypothesis (H₁) is accepted.